If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2(2x + 3) = 21 Reorder the terms: x + -2(3 + 2x) = 21 x + (3 * -2 + 2x * -2) = 21 x + (-6 + -4x) = 21 Reorder the terms: -6 + x + -4x = 21 Combine like terms: x + -4x = -3x -6 + -3x = 21 Solving -6 + -3x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3x = 21 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 21 + 6 -3x = 21 + 6 Combine like terms: 21 + 6 = 27 -3x = 27 Divide each side by '-3'. x = -9 Simplifying x = -9
| 6w=5 | | y=-5x^2+40x | | y=(6x-4)(x+1) | | (3+x)+(y+12)= | | a=1/2(a+5) | | 7m-20=-3m | | (2x-1)(x-5)=0 | | y=2(-1)+6 | | 2(X-36)=3(81-X) | | 5d-11=2d+12 | | 3(x-2y)=9 | | 6+7y=-7 | | x/-3+6=10 | | a=1/2(a-5) | | 2y=3y+10 | | 3X=170-2X | | 4x-12+5=-7 | | 5-7x=-6x | | -4=x-8-2 | | -5r-2(r+3)=11 | | 4x-5(x+3)=14 | | -6=-2x-10 | | 5x-(x-5)+7=15 | | 1/3(2x-4)=3 | | 145+36w=433 | | x-9y=-81 | | -6=-(x+10) | | 1/6x+3/4=5/9 | | 2b+17=11 | | -3=-3x+15 | | 42=96 | | 4-2/3(4x-9)=111 |